1991
DOI: 10.1159/000457493
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of Indomethacin in Preterm Infants

Abstract: 38 preterm infants with symptomatic patent ductus arteriosus received indomethacin intravenously. Plasma samples were collected at 2, 4, 6 or 8 and 12 h after each of 3 doses. Indomethacin, demethylindomethacin and p-chlorobenzoic acid were determined in plasma and urine along with acid-labile metabolites using HPLC. Fifty-eight percent of the infants demethylated indomethacin; half of the unchanged and demethylated drug was found as conjugates in urine; 14% deacylated the drug. Shorter elimination half-life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…In the study by van Overmeire et al (13), indomethacin was started with 0.2 mg kg À1 body weight on day 3 and repeated twice every 12 h. In contrast, Shaffer et al (12) used an individualized pharmacokinetic/pharmacodynamic dosing approach that is based on determinations of plasma indomethacin concentrations, calculation of pharmacokinetic parameters, and repeated evaluation of treatment effect and toxicity. With this approach, they effectively treated premature infants with increased indomethacin clearance due to advanced postnatal age (22). The results of the present study confirm the high rate of PDA closure by indomethacin demonstrated by van Overmeire et al and Shaffer et al (12,13).…”
Section: Discussionsupporting
confidence: 87%
“…In the study by van Overmeire et al (13), indomethacin was started with 0.2 mg kg À1 body weight on day 3 and repeated twice every 12 h. In contrast, Shaffer et al (12) used an individualized pharmacokinetic/pharmacodynamic dosing approach that is based on determinations of plasma indomethacin concentrations, calculation of pharmacokinetic parameters, and repeated evaluation of treatment effect and toxicity. With this approach, they effectively treated premature infants with increased indomethacin clearance due to advanced postnatal age (22). The results of the present study confirm the high rate of PDA closure by indomethacin demonstrated by van Overmeire et al and Shaffer et al (12,13).…”
Section: Discussionsupporting
confidence: 87%
“…In some fetuses indomethacin will cause immediate constriction and possibly closure; in others the ductus can remain open despite repeated doses10. It has been argued that the pronounced difference in effect, in one case11 even observed in twins in which one infant suffered from ductal closure and the other's ductus remained open, is caused by different pathways of breakdown of the drug: by deacetylation or by demethylation12. Several other pharmacological agents have been known to cause ductal constriction; for example, betamethasone, applied to enhance fetal lung maturation, can cause transient reversible ductal constricition13.…”
Section: Discussionmentioning
confidence: 99%
“…(1 mg/kg) and i.m. (1 mg/kg) administrations to sheep, as well as those reported in various domestic animals (Cociglio et al ., 1991; Cristofol et al ., 1996) and humans (Duggan et al ., 1972; Alvan et al ., 1975), including preterm infants (Friedman et al ., 1991), have been best described using a two‐compartment model.…”
Section: Discussionmentioning
confidence: 99%